2015
DOI: 10.5198/jtlu.2015.665
|View full text |Cite
|
Sign up to set email alerts
|

Development of rail infrastructure and its impact on urbanization in the Randstad, the Netherlands

Abstract: Long-term, large-scale empirical studies on the simultaneous development of transport infrastructure and the built environment are scarce. This paper provides a long-term study of the development of the railway network and its impact on the built-up area-and vice versa-using the case study of the Randstad in the Netherlands between 1850 and 2010. The analysis is both qualitative and quantitative. We describe the shares of the built-up area in concentric buffers of 1-kilometer intervals from railway stations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Thus, the overall findings imply that there is an increasing tendency toward a denser spatial structure around the selected rail stations. The results are consistent with the findings by Kasraian et al, (2016) who reported that rail infrastructure prompted further urban growth in the Randstad, the Netherlands, suggesting that urbanization is more likely to occur in the vicinity of the newly opened stations. Although the captured densification around the rail stations is aligned with TOD principles, the success of densification relies on the capacity of existing neighborhoods, and the populations living within those neighborhoods, to adapt to denser ways of living, working, traveling, and socializing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the overall findings imply that there is an increasing tendency toward a denser spatial structure around the selected rail stations. The results are consistent with the findings by Kasraian et al, (2016) who reported that rail infrastructure prompted further urban growth in the Randstad, the Netherlands, suggesting that urbanization is more likely to occur in the vicinity of the newly opened stations. Although the captured densification around the rail stations is aligned with TOD principles, the success of densification relies on the capacity of existing neighborhoods, and the populations living within those neighborhoods, to adapt to denser ways of living, working, traveling, and socializing.…”
Section: Discussionsupporting
confidence: 92%
“…This policy mainly focused on re-concentrating development in major urban centers in response to the suburbanization process which had increasingly taken place in the Netherlands after World War II (Pojani & Stead, 2014). Accordingly, Dutch planning policy actively developed rail lines to link rural communities and small towns to the major cities (Kasraian, Maat, & van Wee, 2016). In this regard, the RandstadRail has emerged from a long-envisioned urban plan in the Randstad South Wing (especially the Rotterdam-The Hague metropolitan area).…”
Section: Context and Empirical Studymentioning
confidence: 99%
“…A rise in the share of rural inhabitants is associated with higher car kilometres. This was expected as the "rural" category includes municipalities in the Green Heart and the Randstad's outer ring which mostly lack an efficient and well-connected rail infrastructure, have less disincentives for car use and more space for parking (Kasraian et al, 2016a). Areas on higher distances from motorway exits are most likely in the Green Heart and outer rings, which also lack proper train connections, thus train and also bicycle kilometres travelled show lower values.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…Rail has supported urban population growth to various extents over different stages of history worldwide (Akgüngör, Aldemir, Ku̧tepeli, Gülcan, & Tecim, 2011;Atack, Bateman, Haines, & Margo, 2010;Beyzatlar & Kustepeli, 2011;da Silveira, Alves, Lima, Alcântara, & Puig, 2011;Kasraian, Maat, & Van Wee, 2015;Kotavaara, Antikainen, & Rusanen, 2011;Mojica & Martí-Henneberg, 2011). Rail can channel the population from a city's core to the periphery (Garcia-López, 2012;Levinson, 2008) and stimulate residential developments (Ratner & Goetz, 2013;Xie & Levinson, 2010).…”
Section: Transport-land Usementioning
confidence: 99%